PLANNING FOR INCREASING LECTURER RESEARCH PRODUCTIVITY: (CASE STUDY: BUILDING ENGINEERING EDUCATION STUDY PROGRAM, UNIVERSITAS NEGERI JAKARTA) - Yusrina Luthfiana; Qomariyatus Sholihah; Moh. Said (LPPM Universitas Negeri Jakarta, 2024)
The World Class University trend in higher education has an impact on the need for planning in the research aspect because the quantity and quality of research are very influential in global university rankings. This research explores planning strategies as well as challenges and obstacles in efforts to increase the research productivity of lecturers in the Building Engineering Education Study Program, Universitas Negeri Jakarta based on the perspective of the study program coordinator. This research uses a qualitative descriptive approach using data collection techniques in the form of documentation complete with interviews with the study program coordinator. Some of the plans carried out by the study program to increase lecturer research productivity include the 1 lecturer 1 publication per year program, expanding cooperation and collaboration with national and international universities in research and scientific publications, holding international scientific article publication workshops, initiating collaboration with industry in the field of research and forming a research team of lecturers. The obstacles and challenges faced by the study program include lecturer workload, resources, funding, and research administration burden.